Targeting pericyte differentiation as a strategy to modulate kidney fibrosis in diabetic nephropathy - Humphreys, Benjamin D. (2012)
Pericytes are a heterogeneous group of extensively branched cells located in microvessels where they make focal contacts with endothelium. Pericytes stabilize blood vessels, regulate vascular tone, synthesize matrix, participate in repair and serve as progenitor cells, among other functions. Recent work has highlighted the role of pericytes and pericyte-like cells in fibrosis, where chronic injury triggers pericyte proliferation and differentiation into collagen-secretory, contractile myofibroblasts with migration away from vessels, causing microvascular rarefaction. In this review I summarize the developmental origins of kidney pericytes and perivascular fibroblasts, discuss pericyte to myofibroblast transition in type I diabetic nephropathy and describe the regulation of pericyte differentiation into myofibroblasts as a therapeutic target for treatment of diabetic nephropathy.